Retroperitoneoscopic nephrectomy for a nonfunctioning kidney - Sekulić, Vuk; Bogdanović, Jovo; Herin, Ranko; Djozić, Senjin; Popov, Mladen (Vojnosanitetski pregled, 2021)
Background/Aim. The minimally invasive laparoscopic nephrectomy was first performed in 1991. The objective of this paper was to present the surgical technique of retroperitoneoscopic nephrectomy and to our experience with this procedure in removal of non-functioning kidneys. Methods. This retrospective study enrolled 55 patients who underwent retroperitoneoscopic nephrectomy at our institution during the period from January 2011 to November 2016. All patients had a unilateral non-functioning kidney confirmed by intravenous or computed tomography (CT)-urography and renal scintigram. Their medical records were analyzed for demographic data, duration of surgery, average blood loss, duration of hospital stay as well as time to return to normal life activities. Results. The mean age of patients was 43 years (range 23–78). Perioperative or early postoperative mortality was not recorded. Mean operative time was 82 minutes (range 45–210). The average blood loss was 90 mL (40–450). The average hospital stay was 4 days (3–7). Return to life activity was in average after 12 days (9–15). Conclusions. Retroperitoneoscopic nephrectomy for a non-functioning kidney is a feasible, safe, and effective minimally invasive method. The length of hospital stay and convalescence was shorter than after open nephrectomy.